Malta : Report on the Observance of Standards and Codes-Data Module; Response by the Authorities; and Detailed Assessments Using the Data Quality Assessment Framework. (IMF Staff Country Reports; Country Report ;, 2006)
The quality of the macroeconomic statistics for Malta has improved significantly in recent years, particularly as a result of the legal and institutional restructuring of the National Statistics Office (NSO). These changes were made in an effort to respond more effectively to the needs of users and to comply with new data-reporting requirements of the European Union (EU). These improvements have brought Malta's statistical practices in line with internationally accepted standards and practices in a number of statistical areas.